2007
DOI: 10.1038/sj.onc.1210508
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor ZEB1 (δEF1) promotes tumour cell dedifferentiation by repressing master regulators of epithelial polarity

Abstract: Epithelial to mesenchymal transition (EMT) is implicated in the progression of primary tumours towards metastasis and is likely caused by a pathological activation of transcription factors regulating EMT in embryonic development. To analyse EMT-causing pathways in tumourigenesis, we identified transcriptional targets of the E-cadherin repressor ZEB1 in invasive human cancer cells. We show that ZEB1 repressed multiple key determinants of epithelial differentiation and cell-cell adhesion, including the cell pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
483
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 549 publications
(533 citation statements)
references
References 39 publications
35
483
2
5
Order By: Relevance
“…Furthermore, expression profiling revealed a significant overlap between the gene sets affected by Fra-1 in EpH4 cells and data sets from human breast cancer cell lines, in which Zeb1 or Zeb2 expression had been targeted. 34,35 Consistent with the data from human cells, 14 RNA interference demonstrated that reducing the expression of Zeb1 and Zeb2, and to a lesser extent Zeb2 in EpFra1 cells, restored the expression of E-cadherin and most Zeb target genes and reduced migration and invasion in vitro. Interestingly, Zeb2 was decreased in Zeb1 knockdown cells and increased upon ectopic Zeb1 expression.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, expression profiling revealed a significant overlap between the gene sets affected by Fra-1 in EpH4 cells and data sets from human breast cancer cell lines, in which Zeb1 or Zeb2 expression had been targeted. 34,35 Consistent with the data from human cells, 14 RNA interference demonstrated that reducing the expression of Zeb1 and Zeb2, and to a lesser extent Zeb2 in EpFra1 cells, restored the expression of E-cadherin and most Zeb target genes and reduced migration and invasion in vitro. Interestingly, Zeb2 was decreased in Zeb1 knockdown cells and increased upon ectopic Zeb1 expression.…”
Section: Discussionsupporting
confidence: 73%
“…GSEA revealed that the promoters of the downregulated genes were enriched with TRE/CRE motifs, bound by AP-1, but also with E-boxes bound by Zeb/Slug proteins (Supplementary Table S1). Importantly, a significant overlap was found between the EpFra1 downregulated gene set and the genes upregulated in MDA-MB-231 cells following ZEB1 knockdown, 34 as well as genes modulated by ectopic ZEB2 expression in A431 cells 35 (Table 1b, Supplementary Figure S6d). Besides E-cadherin, decreased expression of several Zeb1/Zeb2 transcriptional targets, including polycistrons encoding for the miR-200 family, was confirmed by qRT-PCR (Figure 5c) and the expression of Zeb targets was largely restored upon Fra-1 knockdown (Supplementary Figure S6e).…”
Section: Resultsmentioning
confidence: 99%
“…showed that PI(3) kinase contributes to TrkB signaling as well (including anoikis resistance; Douma et al, 2004), in aggregate these data suggest a model in which TrkB activates multiple pathways, some of which critically depend on Zeb1 (Figure 7). Several reports have shown a correlation between Zeb1 expression and the aggressiveness of tumors, including those of endometrial (Spoelstra et al, 2006;Singh et al, 2008), colon (Pena et al, 2005;Aigner et al, 2007b), breast (Aigner et al, 2007a), lung (Dohadwala et al, 2006), gallbladder (Adachi et al, 2009), ovarian (Bendoraite et al, 2010) and prostate origin (Graham et al, 2008). In colon cancer, Zeb1 expression is linked to loss of the basement membrane, which correlates with increased metastasis (Spaderna et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, ZEB factors and miR200 reciprocally control their expression in a strict feedback loop [133]. Of note, ZEB1 is a key EMT regulator in many human cancers including prostate, colon, breast and pancreatic [132,[134][135][136], while miR200 family members are often down-regulated in cancer cells [131]. Actually, the regulation of EMT by miRNAs is a very general phenomenon not limited to TrkB signalling [137].…”
Section: Taddei Et Almentioning
confidence: 99%